Standards for Facilities and Infrastructure in Building Quality Education in Senior High Schools - Khairullah, Ridho; Fatayan, Arum; Syarif, Moh Suryadi; Ghani, Abd. Rahman A (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The intent of this study is to evaluate and measure the gaps in various components—design, installation, process, and product—so that it can provide information for improvement and development related to the Facilities and Infrastructure Standards in Building Educational Quality at Senior High School. The evaluation model approach used in this study is the Discrepancy Evaluation Model, developed by Malcolm Provus. This research method is a mixed method, not only qualitative, descriptive, and evaluative but also quantitative, and it combines both. The evaluation subjects were 12 people, including principals, vice principals, educators, parents, committees, and supervisors at Fatahillah Ciledug Senior High School, Tangerang City. The evaluation findings indicate that the gap or discrepancy in the design aspect is 70% according to the standard indicators of facilities and infrastructure, based on the reference criteria categorized as "High/Sufficiently Appropriate." For the installation aspect, the gap level is 75% on the standard indicators of facilities and infrastructure, which falls into the category of "High/Good." Additionally, there is a gap level of 37% on the same standard indicators, placing it in the category of "Medium/Good." For the process aspect, the gap level of 37% on the standard indicators of facilities and infrastructure with reference to the discrepancy/inequality reference criteria is included in the category of “Medium/Good,” and for the product aspect, the gap or inequality level is 39%. This rating is after consulting the reference criteria of discrepancy/inequality.